Volatile disease markers of American foulbrood-infected larvae in Apis mellifera. (April 2020) - Lee, Sujin; Lim, Sooho; Choi, Yong-Soo; Lee, Myeong-lyeol; Kwon, Hyung Wook
Graphical abstract: Highlights: American foulbrood infected Apis mellifera larvae release disease-specific volatiles. 2 fatty acids and 1 methyl ketone were identified as volatile disease markers (VDMs). Hygienic aged bees showed higher olfactory sensitivity to these VDMs than foragers. These VDMs might be considered as the potential cues for hygienic behavior. Abstract: The honey bee, which lives in the crowded environment of a social hive, is vulnerable to disease infection and spread. Despite efforts to develop various diagnostic methods, American foulbrood (AFB) caused by Paenibacillus larvae infection has caused enormous damage to the apicultural industry. Here, we investigated the volatile organic compounds derived from AFB. After inoculation of the AFB pathogen in honey bee larvae under lab conditions, we identified propionic acid, valeric acid, and 2-nonanone as volatile disease markers (VDMs) of AFB infection using GC/MS. Electrophysiological recordings demonstrated that middle-aged bees, the hygienic-aged bees, are more sensitive to these VDMs than the foragers. Thus, these VDMs have the potential to be efficient and significant cues for worker detection of AFB infected larvae in bee hives. This study supports the idea that the specific olfactory sensitivity of different worker bees depends on their tasks. Taken together, our finding is crucial and sufficient to develop novel disease volatile markers associated with honey bee diseases to diagnose and study the molecular and neural correlates of given hygienic behavior detecting these volatile chemicals by honey bees.